Orthostatic stress causes immediately increased blood pressure variability in women with vasovagal syncope. Issue 127 (April 2016) - Reulecke, S.; Charleston-Villalobos, S.; Voss, A.; González-Camarena, R.; González-Hermosillo, J.; Gaitán-González, M.J.; Hernández-Pacheco, G.; Schroeder, R.; Aljama-Corrales, T.
Highlights: Nonlinear dynamic analysis shows sympathetic and vagal activities fluctuations. Hemodynamic analysis did not show any statistical differences between subjects. Blood pressure variability showed the highest differences between CON and SYN. In patients, systolic blood pressure variability increased immediately after tilt-up. Healthy women show a stable sympatho-vagal balance during orthostatic phase. Abstract: The cardiovascular and respiratory autonomic nervous regulation has been studied mainly by hemodynamic responses during different physical stressors. In this study, dynamics of autonomic response to an orthostatic challenge was investigated by hemodynamic variables and by diverse linear and nonlinear indices calculated from time series of beat-to-beat intervals (BBI), respiratory cycle duration (RESP), systolic (SYS) and diastolic (DIA) blood pressure. This study included 16 young female patients (SYN) with vasovagal syncope and 12 age-matched female controls (CON). The subjects were enrolled in a head-up tilt (HUT) test, breathing normally, including 5 min of baseline (BL, supine position) and 18 min of 70° orthostatic phase (OP). To increase the time resolution of the analysis the time series were segmented in five-minute overlapping windows with a shift of 1 min. Hemodynamic parameters did not show any statistical differences between SYN and CON. Time domain linear analysis revealed increased respiratory frequency and increased blood pressure variability (BPV) in patients during OP meaning increased sympathetic activity and vagal withdrawal. Frequency domain analysis confirmed a predominance of sympathetic tone by steadily increased values of low over high frequency power in BBI and of low frequency power in SYS and DIA in patients during OP. The nonlinear analysis by symbolic dynamics seemed to be highly suitable for differentiation of SYN and CON in the early beginning of OP, i.e., 5 min after tilt-up. In particular the index SYS_plvar3 showed less patterns of low variability in patients reflecting a steadily increase in both BPV and sympathetic activity. The proposed dynamical analysis could lead to a better understanding of the temporal underlying mechanisms in healthy subjects and patients under orthostatic stress.